The Politics of ‘Unplanning’ of Languages in Nepal - Giri, Ram Ashish (Journal of NELTA, 2010)
The elites, who have held power in Nepal since its inception in the eighteenth century, have deliberately ignored issues related to minority/ethnic languages in favour of the languages of their choice. While this ‘unplanning' of languages has been responsible for the loss of scores of languages, it has helped the elites to achieve ‘planned' linguistic edge over the speakers of other languages. This article outlines the sociopolitical and linguistic pretexts of the ‘unplanning' of languages which favours Nepali and English, and explains why privileging of Nepali and English, essential though they are for education, employment and access to the world resources, has, in the existing situation, done more harm than good. Key words: language planning, unplanning of languages, multilingualism, linguistic elitism, hegemony DOI: 10.3126/nelta.v14i1.3089 Journal of NELTA Vol.14, No 1&2, 2009 December Page: 32-44